Structural optimization of transmission line tower based on improved fruit fly optimization algorithm. (October 2022) - Cheng, Juanhan; Shi, Tao
Abstract: Aiming at the problem that fruit fly optimization algorithm is easy to fall into premature, which leads to poor optimization effect, a transmission line tower junction optimization based on the improved fruit fly optimization algorithm is proposed. The flight radius of individual fruit flies is weighted by the number of iterations, to improve the global optimization ability in the early stage and the local optimization ability in the later stage. The average value of the fruit fly population is used to fuse the optimization trend information, which can prevent the algorithm from falling into prematurity and improve the stability of the algorithm. Finally, the calculation method of concentration decision value is optimized, which enhances the ability of the algorithm to jump out of local optimization. Test simulation results show that the improved algorithm proposed has a better effect on solving optimization problems and optimization of transmission line tower structure.